Employment preferences of job applicants: unfolding employer branding determinants. Issue 6 (8th June 2015) - Jain, Neetu; Bhatt, Prachi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – In the ever increasing competition in the employment market, an organization's need to become a "great place to work" has gained significant momentum. Employer branding has thus emerged as an essential management practice employed by the organization to create its image as desirable employer in the eyes of prospective employees. The purpose of this paper is to highlight the understanding of employer branding through the eyes of "potential" young employees in Delhi and North Central Region, India. The results presented in this paper throw light on the perceived importance of employer branding among the prospective employees via analysis of various branding factors chosen for the study. The study results report that the perceived significance of employer branding factors differs mainly across gender and age of prospective employees. Notably, public and private sectors are being perceived significantly different by the potential job applicants on employer branding factors. Thus, this paper presents important findings enabling employers to build brand value and an attractive reputation in the job market so as to attract and retain the best talent. Design/methodology/approach – Survey methodology was used to test the hypothesis. The sample was selected from Delhi and National Capital Region (NCR) primarily from the students of business schools who were randomly selected to fill in the questionnaire. As they are the potential hires, it seemed appropriate to know their preference of employer branding factors. They are ready to join the corporations therefore, data extracted would be much more suitable as they can throw light on their immediate preferences and provide insight into the research study. For collection of data an online structured questionnaire was administered. A total of 270 questionnaires were administered and 239 filled questionnaires were received. Findings – From the results it can be seen that private sector emerged as preferred sector of choice for the majority of potential employees. However, there are some factors which are handled well in private sector as compared to public sector and vice versa. There are some factors like – stability of the company, work-life balance and job security which potential employees perceive as important and therefore, need to be addressed by both public and private sector organizations. Research limitations/implications – Limitation of this study is that the findings cannot be generalized therefore, provide opportunities for further research. Moreover, the sample included only students as prospective employees seeking a new job or a career change. Thus the results obtained on a sample of relatively inexperienced job seekers, might partially reflect commonly held stereotypes of attractive organizations. Hence, it is interesting to use other samples such as experienced job seekers or those who are currently employed. Another limitation is that the study is restricted to Delhi and NCR region hence, the data is not representative of a wider population. Further research may expand the scope in terms of sample size as well. Future research may also explore the extent of employee attraction and retention vis-à-vis employer branding factors in organizations. A final avenue for future studies consists in exploring the processes which underlie the organizational choice decisions of prospective applicants. Practical implications – This study has added to the growing body of research on employer branding factors by generating more knowledge and arguments in favor of certain employer branding factors in the workplace. If organizations truly want to attract good talented people then management needs to bring about the necessary organizational support and infrastructure at the early and middle stages of an employee's career which are most often the stages where important choices are made. They need to be more considerate toward employee needs. Efforts can be made to build a good work culture by paying heed to their preferences. Therefore, this study helps establish a foundation for implementation of various employer branding factors which are perceived important by the potential job applicants, especially in Indian context. The findings are of particular important for human resource (HR) managers and policy makers in both public sector as well as private sectors in these times of increased inter-sectoral personnel movement. These findings can be utilized as a guiding instrument while inter-sectoral recruitment is being made. These would also enable employers to take appropriate action in order to build their employer brand based on certain discussed employer branding factors so as to attract talent which in turn would also help them in retaining talent. Social implications – There are many employer branding factors which tend to affect the mindset of potential employees in selecting their prospective employer. Employers can therefore, endeavor to understand those factors at length so as to attract talent which in turn would also help in retaining talent. Originality/value – Results throw light on the perceived importance the potential employees give to various employer branding factors taken for the study. Perceived significance attached to employer branding factors differs across gender, age, education background, etc. It was also found that for some important employer branding factors public and private sectors are being perceived significantly different by the potential job applicants. Thus, paper presents important findings that would enable employers to take actions in order to build their employer brand so as to attract talent which in turn would also help them in retaining talent.